1984
DOI: 10.1159/000194676
|View full text |Cite
|
Sign up to set email alerts
|

Grass Pollen Allergoid

Abstract: In an open comparative study with 31 grass pollen-allergic patients, two allergen extracts (‘allergoid’ extract/semi-depot extract) were examined. In the 1st year of treatment the allergoid group showed better results in relation to symptom score, drug consumption and IgG response, however, in the course of further treatment this difference was not evident anymore. Treatment was successful in both groups. A significant correlation between total antigen dose and IgG response was found. The better clinical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Baumgarten et al (2) have described in detail SN in relation to hyposensitization with aluminium extracts and reported the same frequency of nodules as in the present study. They have proved aluminium deposits in the vacuoles of the macrophages, and concluded that granulomas are caused both by immunological reactions and hy foreign body reactions due to SN stimulation by seasonal pollen exposition in some patients (this was the case in only one patient in the present investigation).…”
Section: Subcutaneous Nodulessupporting
confidence: 87%
See 1 more Smart Citation
“…Baumgarten et al (2) have described in detail SN in relation to hyposensitization with aluminium extracts and reported the same frequency of nodules as in the present study. They have proved aluminium deposits in the vacuoles of the macrophages, and concluded that granulomas are caused both by immunological reactions and hy foreign body reactions due to SN stimulation by seasonal pollen exposition in some patients (this was the case in only one patient in the present investigation).…”
Section: Subcutaneous Nodulessupporting
confidence: 87%
“…The abscesses and skin necroses characteristic in guinea pig trials (33) have not been shown. The granulomas described in biopsy were histologically in the order of 4-6 weeks old (2).…”
Section: Subcutaneous Nodulesmentioning
confidence: 99%
“…Additionally, the study was solely observational in a selective population without a placebo cohort and could not be compared against healthy individuals. Nonetheless, the observed data are in line with previously reported data from allergoid AIT treated patients [ 1 , 40 , 41 ]. We added to this existing knowledge on allergoid AIT, by studying the accompanying T cell changes during the course of a pre-seasonal allergoid AIT.…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of allergoid AIT with extracts from airborne sources has been extensively described in mouse and human studies, but the measures in these studies were mostly the clinical improvement or the anticipated protective antibody response [ [38] , [39] , [40] , [41] , [42] ]. However, around the millennium Fiebig et al stimulated PBMC of allergic donors with grass pollen allergoids to obtain allergen-reactive T cell lines [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%